Mitochondrial-targeted Aryl Hydrocarbon Receptor and the Impact of 2,3,7,8-Tetrachlorodibenzo-p-Dioxin on Cellular Respiration and the Mitochondrial Proteome - Hwang, Hye Jin (Toxicol Appl Pharmacol, 2016)
The aryl hydrocarbon receptor (AHR) is a ligand-activated transcription factor within the Per-Arnt-Sim (PAS) domain superfamily. Exposure to the most potent AHR ligand, 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), is associated with various pathological effects including metabolic syndrome. While research over the last several years has demonstrated a role for oxidative stress and metabolic dysfunction in AHR-dependent TCDD-induced toxicity, the role of the mitochondria in this process has not been fully explored. Our previous research suggested that a portion of the cellular pool of AHR could be found in the mitochondria (mitoAHR). Using a protease protection assay with digitonin extraction, we have now shown that this mitoAHR is localized to the inter-membrane space (IMS) of the organelle. TCDD exposure induced a degradation of mitoAHR similar to that of cytosolic AHR. Furthermore, siRNA-mediated knockdown revealed that translocase of outer-mitochondrial membrane 20 (TOMM20) was involved in the import of AHR into the mitochondria. In addition, TCDD altered cellular respiration in an AHR-dependent manner to maintain respiratory efficiency as measured by oxygen consumption rate (OCR). Stable isotope labeling by amino acids in cell culture (SILAC) identified a battery of proteins within the mitochondrial proteome influenced by TCDD in an AHR-dependent manner. Among these, 17 proteins with |fold changes| ≥ 2 are associated with various metabolic pathways, suggesting a role of mitochondrial retrograde signaling in TCDD-mediated pathologies. Collectively, these studies suggest that mitoAHR is localized to the IMS and AHR-dependent TCDD-induced toxicity, including metabolic dysfunction, wasting syndrome, and hepatic steatosis, involves mitochondrial dysfunction.